2012
DOI: 10.5483/bmbrep.2012.45.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Smads, p38 and ERK1/2 are involved in BMP9-induced osteogenic differentiation of C3H10T1/2 mesenchymal stem cells

Abstract: Although previous studies have demonstrated that BMP9 is highly capable of inducing osteogenic differentiation of mesenchymal stem cells, the molecular mechanism involved remains to be fully elucidated. In this study, we showed that BMP9 simultaneously promotes the activation of Smad1/5/8, p38 and ERK1/2 in C3H10T1/2 cells. Knockdown of Smad4 with RNA interference reduced nuclear translocation of Smad1/5/8, and disrupted BMP9-induced osteogenic differentiation. BMP9-induced osteogenic differentiation was block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 27 publications
4
73
0
Order By: Relevance
“…It has been demonstrated that the roles of BMP9, 8-prenylnaringenin tigogenin, and other substances can activate the p38MAPK signaling pathway and promote osteogenic differentiation of BMMSCs [2,[4][5][6]. This collectively shows that the p38MAPK signaling pathway may play an important role in the osteogenic differentiation of BMMSCs.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been demonstrated that the roles of BMP9, 8-prenylnaringenin tigogenin, and other substances can activate the p38MAPK signaling pathway and promote osteogenic differentiation of BMMSCs [2,[4][5][6]. This collectively shows that the p38MAPK signaling pathway may play an important role in the osteogenic differentiation of BMMSCs.…”
Section: Discussionmentioning
confidence: 75%
“…Osterix knockout mice eventually succumb due to breathing difficulties and histological results have shown that there is no mineralization reaction in mice embryos. Neither endochondral ossification nor membrane ossification was completed [28][29][30]. ALP, OCN, and COL I are typically used in identification of osteogenic differentiation in cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p38 MAPK is essential for BMP9-induced osteogenesis in mesenchymal progenitor cells (49,54,55). However, BMP9 failed to activate p38 MAPK in 143B cells (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, BMP9, as a new class of BMP, has been widely studied for its strong impact on the induction of MSC differentiation. However, its mechanism and correlation with traditional transforming factors remain unknown (Xu et al, 2012). In this study, we found that BMP9 mainly affects MSC differentiation through the mitogen-activated protein kinase (MAPK) pathway.…”
Section: Introductionmentioning
confidence: 81%